Sikap Etis Gereja Terhadap Perceraian dan Pernikahan Kembali - Stevanus, Kalis (KURIOS, 2018)
This paper aims to expose the ethical attitude of the church in dealing with divorce and remarriage in order to be useful as an input for the pastoral ministry in taking handle with those who are going to divorce, has been divorced or who has remarried. By using an analytical descriptive on texts such Matthew 5:32; 19: 9; Mark 10: 11-12; Luke 16:18, and 1 Corinthians 7: 10-11, then the following results are obtained: First, Christian marriage is a monogamous and wholly partnership(indestructible); second, adultery destroys the foundation of marriage, but it should not be a legal reason for divorce; third, divorce never recommended or ordered; fourth, only the separation is allowed, not the divorce due to the goal of reconciliation; fifth, remarriage with the person who has been divorced is a transgression; sixth, the settlement of divorce and remarriage issues that have occurred is the responsibility of the believers communally (whole) to regain those who have separated from their partners.   Abstrak Artikel ini bertujuan untuk memaparkan sikap etis gereja dalam menyikapi perceraian dan pernikahan kembali agar bermanfaat sebagai bahan masukan bagi pelayanan pastoral gereja https://alimentoshoy.acta.org.co/ dalam menangani anggota warganya yang hendak bercerai, telah bercerai atau yang menikah kembali. Dengan penggunaan metode analisis-deskriptif terhadap teks-teks seperti: Matius 5:32; 19:9; Markus 10:11-12; Lukas 16:18 dan 1 Korintus 7:10-11, maka diperoleh hasil: Pertama, pernikahan Kristen merupakan persekutuan yang bersifat monogami dan seumur hidup (tak terceraikan); kedua, perzinahan merusak fondasi pernikahan, tapi hal itu tidak boleh dijadikan alasan legal untuk bercerai; ketiga, perceraian tidak pernah dianjurkan maupun diperintahkan; keempat, hanya perpisahan yang diperbolehkan, bukan perceraian dengan tujuan untuk rekonsiliasi; kelima, pernikahan kembali dengan orang yang sudah bercerai merupakan pelanggaran (kesalahan); keenam, penyelesaian masalah perceraian dan pernikahan kembali yang telah terjadi adalah tanggung jawab warga gereja secara komunal (keseluruhan) untuk mendapatkan kembali mereka yang telah berpisah dari pasangannya.